Diagnostic, prognostic and predictive value of MicroRNA-21 in breast cancer patients, their daughters and healthy individuals - Usmani, Ambreen (Am J Cancer Res, 2015)
MicroRNA-21 (miR-21) located on 17q23.1 expressed in breast cancer has anti-apoptotic ability and causes tumor cell growth. It is also involved in functions such as signal transduction pathways effecting normal cell growth and differentiation. The primary objective of the study was to identify presence of miR-21 in the serum levels of stage III invasive ductal carcinoma patients and compare its expression with age matched healthy individuals and daughters of index cases. The secondary objective was to evaluate the significance of serum miR-21 gene expression with histologically proven estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) proteins. A total of 132 subjects were recruited: 50 (cases) of stage III invasive ductal carcinoma patients who had not undergone any chemotherapy or surgery were randomly picked with exclusion of females with other types of breast carcinoma. Age-matched, 50 healthy individuals (control A) were selected by purposive sampling after confirmation of no palpable lump/s in their breasts together with 32 daughters of index cases (control B). Serum tests were run on Real Time quantitative Reverse Transcription PCR, threshold cycle was determined and fold change calculated.Normality of continuous variables was assessed by Shapiro-Wilk’s test, groups compared by student t-test, Mann-Whitney test and Fisher exact test, P-value ≤ 0.05 was considered significant. We observed that miR-21 was significantly higher in cases as compared to control A and B (P = 0.001) however control B showed significant gene expression as compared to control A (P = 0.001). The cases were also divided as positive or negative for ER, PR and HER2. High expression of miR-21 in females with stage III invasive ductal carcinoma had been calculated as compared to its age matched healthy subjects. It was observed that triple negative cases showed a greater expression of gene as compared to other groups (P = 0.001). Expression of miR-21 in daughters of the cases was significantly higher as compared to healthy controls but lesser than females with invasive intraductal carcinoma. This result strengthens the concept of inheritability of disease with prediction of miR-21 as a potentially strong diagnostic and prognostic biomarker of breast cancer.